AAMP 98 カンソク キカン チュウ ノ ニーオルスン デノ マイクロパルス・ライダー カンソク - 塩原, 匡貴; シオバラ, マサタカ; 柴田, 隆; シバタ, タカシ; Shiobara, Masataka; Shibata, Takashi (2002)
P(論文) 雲とエアロゾルの後方散乱プロファイルを長期的に観測するために，マイクロパルス ・ ライダー（MPL）をスパールパル諸島ニーオルスンにあるラベン観測所に設置し，1998年より観測を開始した．本報告では，北極閤航空機観測計画1998年キャンペー ン（AAMP 98）期間中に得られたMPLの観測データをもとに，春季北極の雲とエアロゾルの特徴とMPLの観測性能について議論する． In order to acquire long-term data sets of backscatter profiles of clouds and aerosols in the Arctic, a Micro-pulse Lidar (MPL) system was placed at Rabben Observatory in Ny-Alesund、Svalbard and measurement started in 1998. Based on preliminary analysis of the MPL data acquired for the Arctic Airborne Measurement Program 1998 (AAMP 98), features of clouds and aerosols in the Arctic spring are shown; the performance of MPL for cloud and aerosol measurements is discussed in this paper. departmental bulletin paper